Antibacterial activities of Leaf extracts of Indian Bay leaf (Cinnamomum tamala) against Staphylococcus aureus, Salmonella typhi, and Pseudomonas aeruginosa - Rasna, Shompa Sharmin; Afrin, Munira; Nahida, Nazmun Nahar; Nishi, Manira Khanam (Journal of Monno Medical College, 2026)
Background: Natural herbal remedies have shown promising antimicrobial properties and fewer side effects than synthetic antimicrobial agents. Objective: The purpose of the present study was to investigate the antibacterial activities of Indian bay leaf extracts against Staphylococcus aureus, Salmonella typhi, and Pseudomonas aeruginosa. Methodology: This experimental study was carried out from July 2019 to June 2020 in the Department of Pharmacology and Therapeutics with the collaboration of the Department of Microbiology at Mymensingh Medical College, Mymensingh, Bangladesh. The antibacterial activity was tested at different concentrations (20, 10, 5,2.5, 1.25 & 0.625 mg/ml) of both spice extracts by using the disc diffusion & broth dilution method. The extracts were prepared by using solvents aqueous & methanol. The test microorganisms were also tested for their activity against a standard antibiotic Gentamicin (80 mg) by broth dilution method. The result was compared with that of Aqueous and Methanolic extracts. Results: Salmonella typhi, Staphylococcus aureus, and Pseudomonas aeruginosa were all inhibited by ALE at doses of 15 mg/ml and higher. Pseudomonas aeruginosa was inhibited in the case of MLE at concentrations of 15 mg/ml and higher. At doses of 10 mg/ml, Staphylococcus aureus and Salmonella typhi began to exhibit noticeable activity. The Zone of Inhibition (ZOI) for ALE using the disc diffusion technique varied from 6 to 25 mm at various extract concentrations. Staphylococcus aureus, Salmonella typhi, and Pseudomonas aeruginosa had minimum inhibitory concentrations (MIC) of 10, 15, and 15 mg/ml in ALE and 5, 5, and 7.5 mg/ml in MLE, respectively. Additionally, this finding was compared to that of the common antibiotic Gentamicin, whose MICs were lower than those of ALE and MLE. The current investigation revealed that leaf extracts, both aqueous and methanolic, exhibited antibacterial properties against Salmonella typhi, Pseudomonas aeruginosa, and Staphylococcus aureus. Conclusion: The study observed a definite antibacterial effect of both the aqueous and methanolic extract of leaves of Cinnamomum tamala against Staphylococcus aureus, Salmonella typhi, and Pseudomonas aeruginosa. The physiologically active components of Cinnamomum tamala that give it its antibacterial properties need to be identified and isolated via more research. Journal of Monno Medical College, June, 2025; 11(1) : 9-17